Health and social care professionals' anguish in providing care and support to children who are AIDS orphans in Nelson Mandela Bay: A qualitative study - Sharron Frood; Dalena (R.M.); Esmeralda Ricks (Elsevier, 2018)
Background: Orphanhood is a major consequence of the AIDS pandemic globally. In South Africa most children who are AIDS orphans live in township communities. They are often uncared for and unsupported by the community, and experience recurrent psychological trauma and much personal suffering. This results in health and social care professionals working with these children experiencing professional anguish. Whilst it is known that children who live as AIDS orphans in township communities suffer, there are no empirical studies reflecting the experiences of health and social care professionals providing care and support to these vulnerable children. Objective: To explore and describe the experiences of primary health care nurses, social workers and psychologists caring for and supporting children who are AIDS orphans living in township communities in South Africa. Design: The descriptive phenomenology research design incorporated an exploratory, contextual and descriptive approach. In-depth individual interviews were used to collect data from participants. Setting: Participants were selected using purposive (nurses and social workers) and snowball sampling (psychologists) from four primary health care clinics and twelve satellite health care clinics, all located in township communities in Nelson Mandela Bay, South Africa. The participants were all caring for and supporting children who are AIDS orphans living in these communities. Participants: The primary health care nurses (n = 10) and social workers (n = 8) were selected using criterion-based purposive sampling, whilst snowball sampling was used to select psychologists (n = 6). Participants are referred to as health and social care professionals. Methods: In-depth individual interviews were recorded and transcribed. Independent coders reviewed the data and individually developed themes and subthemes, using thematic analysis. Results: Although it is accepted that health and social care professionals experience anguish whilst providing care and support to AIDS orphan children, this study provides detail of this professional anguish, as presented in the following four main themes: 1) challenges in providing care and support; 2) unique experiences; 3) short-falls related to "best practice" in the health and social care system; and 4) development of holistic care. Conclusions: The data provided deep and descriptive insights related to the anguish of health and social care professionals in caring and supporting the AIDS orphan children. Keywords: AIDS orphans, Primary health care nurses, Psychologists, Social workers, South Africa, Care, Support, Township communities